(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we construct the topological structure of linear 2-normed space. This enable us to dene the concept of open sets in linear 2-normed space and derive an analogue of Baire’s theorem and Banach Steinhaus theorem in linear 2-normed spaces.